Leader–member exchange, employee turnover intention and presenteeism: the mediating role of perceived organizational support. Issue 2 (6th January 2021) - Huang, Ing-Chung; Du, Pey-Lan; Wu, Li-Fan; Achyldurdyyeva, Jennet; Wu, Li-Chang; Lin, Chih Seng
Abstract : Purpose: The purpose of this paper is to report the findings of a study that examines the influence of leader–member exchange (LMX) on employees' turnover intention and presenteeism with the mediating role of perceived organizational support in the context of the semiconductor industry. Design/methodology/approach: An empirical study based on a sample of 124 department managers and 241 team members in five high-tech companies in Taiwan. Structural equation modelling analysis was used for hypothesis testing. Findings: The results reveal that perceived organization support significantly relates to employees' turnover intention and mediates the relationship between LMX and turnover intention. Additionally, employees' presenteeism is influenced by perceived LMX. Practical implications: The results of the study are of high importance for high-tech companies, which continuously strive for innovation efficiency and sustainability. Managers and practitioners could benefit from better understanding regarding the importance of perceived organization support and LMX in affecting employee behaviours and company performance. Originality/value: The present study finds a significant positive relationship between LMX and presenteeism, which is contrary to the previous research.